Clinical Significance of Hu-Antigen Receptor (HuR) and Cyclooxygenase-2 (COX-2) Expression in Human Malignant and Benign Thyroid Lesions. - Giaginis, Constantinos; Alexandrou, Paraskevi; Delladetsima, Ioanna; Karavokyros, Ioannis; Danas, Eugene; Giagini, Athina; Patsouris, Efstratios; Theocharis, Stamatios (Pathol Oncol Res, 2016)
Hu-antigen R (HuR) is considered to play a crucial role in tumor formation and growth by binding to mRNAs encoding proteins such as Cyclooxygenase-2 (COX-2) and inducing their expression via mRNA stabilization and/or altered translation. The present study aimed to evaluate the clinical significance of HuR and COX-2 proteins’ expression in human benign and malignant thyroid lesions. HuR and COX-2 proteins’ expression was assessed immunohistochemically on paraffin-embedded thyroid tissues obtained from 98 patients with benign (n = 48) and malignant (n = 50) lesions and was statistically analyzed with clinicopathological parameters, follicular cells’ proliferative capacity and recurrence risk rate. Enhanced HuR and COX-2 expression was significantly more frequently observed in malignant compared to benign thyroid lesions (p = 0.0073 and p = 0.0016, respectively), as well as in papillary carcinomas compared to hyperplastic nodules (p = 0.0039 and p = 0.0009, respectively). Positive associations of both HuR and COX-2 expression with follicular cells’ proliferation rate were also noted (p = 0.0087 and p = 0.0127, respectively). In malignant thyroid lesions, elevated COX-2 expression was significantly associated with female patients’ gender (p = 0.0381) and the presence of lymph node metastases (p = 0.0296). The present data support evidence that both HuR and COX-2 may be involved in the malignant state of thyroid neoplasia and may be utilized in the diagnosis of malignant thyroid tumors.
Keywords: Adult; Aged; Biomarkers, Tumor; Carcinoma, Papillary; Case-Control Studies; Cyclooxygenase 2; ELAV-Like Protein 1; Female; Follow-Up Studies; Humans; Hyperplasia; Immunoenzyme Techniques; Lymphatic Metastasis; Male; Middle Aged; Neoplasm Grading; Neoplasm Invasiveness; Neoplasm Recurrence, Local; Neoplasm Staging; Prognosis; Survival Rate; Thyroid Gland; Thyroid Neoplasms